Linear and Non-linear Mechanical Behavior of Solid Materials - Lexcellent, Christian (Springer International Publishing, 2018)
This book offers an essential introduction to the linear and non-linear behavior of solid materials, and to the concepts of deformation, displacement and stress, within the context of continuum mechanics and thermodynamics. To illustrate the fundamental principles, the book starts with an overview of solid mechanics, experimental methods, classes of material behaviors, and the thermodynamic modeling framework. It then explores linear elastic behavior, thermoelasticity, plasticity, viscoplasticity, fracture mechanics and damage behavior. The last part of the book is devoted to conventional and magnetic shape memory alloys, which may be used as actuators or sensors in adaptive structures. Given its range of coverage, the book will be especially valuable for students of engineering courses in Mechanics. Further, it includes a wealth of examples and exercises, making it accessible to the widest possible audience.